The Role of Materialism-Based Work Culture to Reduce Accounting Fraud - Isnan Murdiansyah (International Journal of Religious and Cultural Studies, 2023)
This study aims to reveal accountants' efforts to reduce fraud. This research uses an interpretive approach with phenomenological methods to see phenomena that are directly related to symptoms that appear around humans who are organized within the scope of interaction between the accounting profession, clients and third parties. The data in this study were obtained from observations in the field by actively participating in each activity, in-depth interviews related to efforts to avoid fraudulent practices with people who are directly involved in the world of accountants. Data analysis was performed using noema and noesis analysis. The results of the study show that the value of materialism is able to reduce fraud by an accountant through fair salary distribution, appreciating the work of employees and instilling a mindset that does not depend on the facilities provided by clients.